From the corner of his eye [large type] - Koontz, Dean R. (Dean Ray), 1945- (Random House Large Print, 2000)
Bartholomew "Barty" Lampion is born on a day marked by tragedy. Both of his parents will die, though thanks to some quick medical help, his mother, Agnes, will return to the living. Little Barty proves himself to be an amazing child almost from the first day -- a prodigy who, by the age of three, is reading at an eighth-grade level. Then tragedy strikes again when a rare type of cancer forces the removal of both of Barty's eyes, leaving him totally blind. Yet despite this setback, Barty continues to amaze everyone with his boundless love of life, his steely determination, and more than a few astonishing perceptions. Angel White is born on the same day as Barty, and the circumstances are just as tragic. Not only was Angel conceived during a violent rape, Angel's mother, Seraphim, a 15-year-old African American and the daughter of a Baptist minister, dies during the birth. But something amazing happens first, something that will affect the lives of both the doctor delivering the child and Seraphim's older sister, Celestina, who raises Angel. This child, too, proves to be exceptional.